Psychological Well-Being Differences Between PNS Lecturers And Non-PNS Lecturers At UIN Raden Fatah Palembang - Listya Istiningtyas (Psikis : Jurnal Psikologi Islami, 2020)
There are two permanent lecturers at UIN Raden Fatah Palembang, namely PNS (Civil Servant) and Non-PNS (Non-Civil Servant) lecturers, but for Non-PNS lecturers there are differences in treatment and legal uncertainty in that status. This study focuses on knowing the differences in psychological well-being between PNS and Non-PNS lecturers at UIN Raden Fatah Palembang. This research is a comparative quantitative study. From 25% of the population the number of research subjects is 125 people (81 PNS lecturers and 44 Non-PNS lecturers). The measuring tool uses for the dimensions of psychological well-being is a modified scale and adapted from Ryff and Keyes (1995). The data analysis method used was the Independent Sample t-test using SPSS 24.0. The result of hypothesis test shows a significance value that states Ha is accepted and H0 is rejected. In conclusion, there is a significant difference between the psychological well-being of PNS lecturers and non-PNS lecturers at UIN Raden Fatah. The mean variant of Non-PNS lecturers is also smaller, meaning that the psychological well-being of PNS lecturers is higher than Non-PNS lecturers.